Differences in Gross Motor Development for Infants 6-12 Months Based on Exclusive Breastfeeding - Manggiasih Dwiayu Larasati (Jurnal Kebidanan, 2023)
Gross motor and large muscle which are basic movement skills. The golden age of motor development is 6-12 months. The impact of basic motoric stages is not passed, namely not having basic motoric conceptions, the long-term effect will affect children's emotional and mental intelligence. One of the factors that influence the process of growth and development is offering breastfeeding exclusively. Breast milk contains taurine which functions as a neurotransmitter and the maturation process of brain cells.. This study aims to observe gross motoric development in infants 6-12 months between those who were exclusively breastfeeding and non-exclusively breast milk at the Sawah Besar Health Center in 2020. The method of this research is an analytic observational study with a cross-sectional approach. The study population was mothers and infants aged 6-12 months at the Sawah Besar Public Health Center in Jakarta. The number of samples was 39 respondents with purposive sampling technique. Data collection used KPSP, KMS and questioner. Statistical analysis using Chi Square test and Logistic Regression. The results of this study are maternal age (p = 0.015), maternal education (p = 0.023), exclusive breastfeeding (p = 0.001) and infant growth (p = 0.003) had an impact on gross motor development of infants aged 6-12 months. It indicates that exclusive breastfeeding is the main factor determining the gross motor development of infants aged 6-12 months. The difference in gross motor development of babies who are given exclusive breastfeeding will be 25,002 times earlier than babies who are non-exclusive breast milk.